+0  
 
0
83
1
avatar

b(5px - 3c) = a(qx - 4)

Guest Aug 20, 2017
Sort: 

1+0 Answers

 #1
avatar+178 
0

Input: b(5px-3c) = a(qx-4)

Intepretation: Solve for \(x\) in \(\)\(b(5px+3c) = a(qx-4)\)

Expand:

\(5bpx-3bc=aqx-4a\)

Move the \(x\) terms to the right, integer ones to the left:

\(5bpx-aqx=3bc-4a\)

Pull the x out from the left term:

\((5bp-aq)x=3bc-4a\)

Divide both sides by \(5bp-aq\):

\(x=\frac{3bc-4a}{5bp-aq}\)

Done :D

Jeffes02  Aug 20, 2017

9 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details